Nostalgic marketing, perceived self-continuity, and consumer decisions. Issue 8 (19th September 2016) - Ju, Ilyoung; Kim, Jihye; Chang, Mark Jaewon; Bluck, Susan
Abstract : Purpose: The purpose of this paper is to examine the effects of nostalgic marketing on consumer decisions, including the relation of nostalgia to perceived self-continuity, brand attitude (BA), and purchase intent (PI). Design/methodology/approach: The study uses an experimental design that compares individuals' responses to past-focussed (nostalgic) vs present-focussed (non-nostalgic) advertising across a range of three product types. Analyses include structural equation modeling (SEM) to investigate direct and mediated relationships. Findings: Nostalgic past-focussed advertisements (as compared to present-focussed advertisements) elicited higher perceived self-continuity which led to more favorable ratings of BA and greater intent to purchase the product. These effects held up regardless of product type. SEM showed that the relation of advertising-evoked nostalgia to BA is partially mediated by consumer's perceived self-continuity. BA also directly predicted PI. Practical implications: These findings provide two implications for marketing managers. First, the perceived self-continuity plays an important role in the success of nostalgia marketing. As such, advertising designed to directly influence perceived self-continuity should be used for framing a nostalgic marketing purposes that aims to connect consumers to particular brands. Second, evoking nostalgia in marketing communications is not just effective for one product type but appears to be useful across a variety of product type (i.e. utilitarian, hedonic, and neutral). Originality/value: The study is based within an experiential marketing framework but is innovative in examining the specific experience of nostalgia and linking it to consumer's identity (i.e. self-continuity). This area has received little attention and appears to be a promising area for future research on consumer decisions.